Komunikasi Dialogis Krisis di Instagram: Analisis Respons Terra Drone terhadap Opini Publik Pasca Kebakaran - Arrasyifah Leby; Saeful Mujab; Abellia Nathany; Syafaat Ariski (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines Terra Drone Indonesia's implementation of management dialogue in addressing crisis communication following a fire at the company's office building. The incident sparked a wave of negative sentiment on Instagram, marked by increased public comments assessing occupational safety, data security, and the company's transparency in conveying information related to the legal process. The study used a qualitative approach with a case study method to understand how the company developed a crisis communication strategy through official statements published on social media. Data were analyzed based on dialogic elements of communication, particularly empathy for victims, humanitarian commitment, and the company's position and normative and defensive stance in affirming legal handling and compliance measures. The results show that the company attempted to balance an empathetic narrative to mitigate public pressure with a defensive strategy to maintain institutional legitimacy. However, the dynamics of public opinion on Instagram indicate that the company's response has not fully met the expectations of two-way communication. This is evident in the dominance of one-way communication patterns and the lack of technical clarifications needed by the public, thus creating a productive economic outlook. Overall, dialogic management has been implemented responsively, but has not been optimal in building a space for dialogue and public trust as a whole.